(untitled) - Edersheim, Elizabeth Haas (Hoboken, NJ, 2004)
Praise for MCKINSEY'S MARVIN BOWER "I had the privilege of working closely with Marvin and McKinsey for many years. This book makes Marvin come to life and perpetuates him as a role model." -Peter F. Drucker "A wonderful book about a wonderful man. In many ways, Marvin's McKinsey framed the hypotheses in our own search for excellence-for example, passion for values, belief in people as the prime resource, and willingness to let people experiment. As well as I thought I knew Marvin, however, this remarkable book, drawing on the collective memories of those who worked most closely with him, taught me a ton about how extraordinary the man really was and what made him that way. Many have called Drucker the man who invented management; I think history will conclude that both he and Marvin Bower share that pedestal." -Bob Waterman coauthor of In Search of Excellence "Marvin Bower became a legend, not just within McKinsey & Company, but within professional services and the business world more broadly. In everything he did and said, he embodied the professional approach and the importance of values. This book sheds remarkable insight on a remarkable man and on the power of constancy of purpose." -Ian Davis Worldwide Managing Director, McKinsey & Co. "It is as Marvin would have wanted it-simple, honest, fact-based, wonderful stories, with a long term perspective. An insightful read about the father of management consulting." -Lois Juliber COO, Colgate Palmolive "This book provides fascinating insight into the early days of modern management consulting. It is an extremely enlightening look at the origin of one of America's most important professions and one of America's most innovative leaders." -Thomas H. Lee
Keywords: Business consultants,Leadership,Cố vấn thương mại,Lãnh đạo